(untitled) (Research, Society and Development, 2020)
Objective: to identify, in scientific production, the knowledge of the nursing team about the safe surgery checklist and the implementation and adherence of this instrument in surgical units. Method: integrative literature review for which primary articles were systematically searched for in the MEDLINE, LILACS AND BEDENF data sources, via the VHL Regional Portal. The searches took place in the second half of 2019. Results: in the studies found, no satisfactory results were observed regarding the nurse’s performance in the application of the checklist, which is an instrument performed by the nursing technician, and the Surgical Center nurse is responsible for actions aimed at managing the caution. Conclusion: the lack of scientific knowledge on the part of the nursing team that works with the checklist stands out and that its implementation and adherence have been occurring in a fragile way. It was pointed out as a need for institutions to invest in promoting actions for quality of care and patient safety, aiming at qualified structures and teams.